2017
DOI: 10.1097/htr.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Pediatricians' Knowledge, Attitudes, and Behaviors to Screening Children After Complicated Mild TBI: A Survey

Abstract: Objective To understand pediatricians’ attitudes, knowledge and behaviors about the care of children with complicated mild traumatic brain injury (TBI). Setting and participants 3500 pediatricians randomly selected from the American Medical Association master file. Design Cross-sectional survey Main measures Pediatricians were asked about their attitude toward following children with complicated mild TBI for cognitive and behavioral sequelae; their knowledge of TBI sequelae; and, their usual evaluation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Further work needs to be done to understand the variations in type of follow‐up care sought by location of residence. Nonetheless, our findings, in line with others, 31,32 highlight the need to formally train PCPs about concussion management and provide them with educational and referral support to care for concussed youth.…”
Section: Discussionsupporting
confidence: 89%
“…Further work needs to be done to understand the variations in type of follow‐up care sought by location of residence. Nonetheless, our findings, in line with others, 31,32 highlight the need to formally train PCPs about concussion management and provide them with educational and referral support to care for concussed youth.…”
Section: Discussionsupporting
confidence: 89%
“…34 Pediatricians report difficulties in referring children to both SLP and neuropsychology. 5 Families who receive Medicaid insurance find access to these providers particularly challenging due to long waits or unavailability, as many of our families reported. 16,35 Addressing children's health care needs is complicated further by the low rate of primary care follow-up.…”
Section: Discussionmentioning
confidence: 88%
“…3,4 Physicians report difficulties in referring children for cognitive and behavioral services due to patient insurance limitations and limited availability of providers. 5 While schools are required to provide services for children with TBI under the Individuals with Disability Education Act (IDEA), 6 schools may not have the resources to identify children in need of services, may be unaware of the TBI, or may be unable to provide them appropriate academic or health care supports. [7][8][9] Over a decade ago, Slomine et al reported on the unmet and unrecognized health care needs of over 300 children hospitalized at least overnight for TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Variable follow-up of TBI patients exists nationally in the United States, ranging from primary care to surgical subspecialties. Primary care providers report discomfort caring for these patients on follow-up, as well as accessing needed resources for problems that arise in these children [ 23 ]. While concussion clinics are increasing in frequency, children with significant head injury with intracranial pathology are inherently different from the typical concussion patient, with high rates of functional impairment, psychosocial dysfunction, and neurocognitive deficits [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%